Evaluation of frame-based and event-by-event motion correction methods for awake monkey brain PET imaging - Jin, Xiao (2014)
PET imaging of non-human primates (NHP) requires correction of head motion if the subjects are scanned awake and their heads are unrestrained, as the NHPs move their heads faster and more frequently than human subjects. This work focuses on designing and validating two motion correction algorithms for awake NHP brain PET imaging. METHODS: Two motion correction methods were implemented for awake NHP brain PET imaging: multi-acquisition frame (MAF) and event-by-event (EBE). Motion data were acquired from an external motion tracking device. The MAF method divides scan data into short subframes, reconstructs each subframe individually and registers them to a reference orientation. This method suffers from residual intra-frame motion and data loss when motion is large as a minimum frame duration is often required. The EBE method, previously implemented for the human brain scanner HRRT and adapted for the microPET FOCUS-220 in this work, eliminates intra-frame motion and should have the best accuracy. We first evaluated the accuracy of both motion correction methods with moving phantom scans on the FOCUS-220. Both motion correction methods were then applied to awake NHP brain PET studies with a GABA(A)-benzodiazepine receptor ligand [(11)C]flumazenil, and the reconstructed images were compared with those from a motion-free anesthetized study. RESULTS: The phantom studies showed that EBE motion correction similarly recovers the contrast (within 3%) as the static study, whereas MAF motion correction using the standard algorithm setting showed 25% reduction in contrast from the static case. In awake NHP brain PET imaging, EBE motion correction better recovers the fine structures than the MAF method, as compared with anesthetized studies. CONCLUSIONS: The large magnitude and frequency of NHP head motion suggests that EBE motion correction with accurate externally measured motion data can noticeably alleviate image blurring due to the intra-frame motion in the MAF motion correction method.